Pengaruh Motivasi, Disiplin dan Kepemimpinan Terhadap Kinerja Pegawai Dengan Budaya Organisasi Sebagai Variabel Intervening Di Dinas Dukcapil Kabupaten Tanah Datar - Zetria, Fauza Dwi; Saputra, Megi; Rizal, Rizal; Pasrizal, Himyar; Fahlefi, Rizal (Jurnal Manajemen Bisnis Syariah, 2025)
This study aims to analyze the effect of motivation, discipline and leadership on the performance of employees of the Dukcapil Service of Tanah Datar Regency which is mediated by organizational culture variables. This type of research is field research with a quantitative approach. The data collection technique used in this research is a questionnaire. The sample used in this study was 33 respondents with total sampling technique. The data analysis technique used is Path analysis. The results showed that motivation and leadership had no effect on organizational culture but discipline had an effect on organizational culture. Motivation has no effect on employee performance while discipline, leadership and organizational culture affect employee performance. Motivation, discipline and leadership have no effect on employee performance through organizational culture. Organizational culture as an intervening variable is not able to mediate the variables of motivation, discipline and leadership so that these three variables have a direct influence on the performance of employees of the Dukcapil Office of Tanah Datar Regency..